Resonance-like structure in ³⁶S(pγ)³⁷Cl reaction - Kachan, A.S.; Vodin, A.N.; Kurguz, I.V.; Lepyoshkina, O.A.; Trotsenko, S.A.; Ushakov, I.V (Вопросы атомной науки и техники, 2004)
The γ-decay of resonances forming resonance-like structure have been investigated in the ³⁶S(pγ)³⁷Cl reaction. The
decay schemes have been established for the first time. The branching ratios and probabilities of direct γ-transitions
have been determined. The assumption that these resonances belong basically to the states of the M1 resonance on the
first excited state in ³⁷Cl has been stated. Position of the M1 resonance has been explained with the account of pairing
forces. У реакції ³⁶S(pγ)³⁷Cl досліджено γ- розпад резонансів, що утворюють резонансноподібну структуру. Уперше
побудовано схеми розпаду, встановлено коефіцієнти гілкування та імовірності прямих γ-переходів.
Висловлено припущення про те, що ці резонанси належать в основному станам М1-резонансу на першому
збудженому стані ядра ³⁷Cl. Положення М1-резонанса пояснюється з урахуванням сил спарювання. В реакции ³⁶S(pγ)³⁷Cl исследован γ-распад резонансов, образующих резонансно-подобную структуру. Впервые установлены схемы распада, определены коэффициенты ветвления и вероятности первичных γ-переходов.
Высказано предположение о том, что эти резонансы принадлежат в основном состояниям М1-резонанса на первом возбужденном состоянии ядра ³⁷Cl. Положение М1-резонанса объясняется с учетом сил спаривания.